The Impact of Migraine and Therapeutic Intervention Methods on Subjective Quality of Life Assessment. Information overview - Mendak , Magdalena; Hanslik, Anna; Białek, Agata; Walczak, Agnieszka; Olszanecka, Monika; Olszanecki , Tomasz; Hovagimyan, Adrian (Quality in Sport, 2025)
Introduction and aim of the study: The main purpose of this article is to describe the role of the psychosomatic influence on our physical health. A large amount of daily stress, having psychiatric disorders, usually distress an internal balance and can initiate a chronic or episodic migraine.This article reviews issue about: pathophysiology of a chronic migraine, migraine disability, quality of life among the patients, predictors, influence on the economic status, self-esteem, relationships. Materials and methods: This article was based on literature gathered from various databases, including Google Scholar, ResearchGate, PubMed, ClinicalTrails, Cochrane database. The keywords migraine, psychosomatics, therapeutic methods, headache, AMPP, IBMS, CaMEO, MIDAS scale were the basis of the review. Results: A comprehensive analysis of the current literature on the pathomechanism of migraine development sheds new light on understanding the nature of the disease. Key factors influencing the development of the disease appear to be the level of stress, coping mechanisms, and the degree of neuroticism. By understanding the risk factors for the development of migraines, we can tailor appropriate therapy based on pharmacological methods and psychotherapy.